STRATEGI HUMAS DALAM SISTEM PENERIMAAN MURID BARU: STUDI KASUS PADA SMK PERINTIS 29 UNGARAN - Aditya, Muhammad; Prima kharismaputra, Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Competition among vocational high schools to attract new students requires schools to implement effective public relations strategies in order to enhance the competitiveness of their promotional efforts. This study aims to analyze public relations strategies used in promoting the New Student Admission System (SPMB) at SMK Perintis 29 Ungaran. The study employs a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model, with validity tested through triangulation of sources and techniques. The results indicate that the effectiveness of promotion is more influenced by direct communication and real-world experiences provided to prospective students than by the mere dissemination of information through promotional media. Demonstrations of vocational program practices and community service activities proved to be the most effective strategies because they build public trust by demonstrating students’ competencies. This study also found that the use of data in planning and evaluating promotional efforts, as well as in managing digital media, still needs to be optimized. The study concludes that the success of vocational school promotion depends on the school’s ability to build relationships and public trust through direct experiences.